Perbandingan Algoritma Fisher-Yates Shuffle Dan Linear Congruent Method Pada Aplikasi Game Susun Ayat Al-Qur’an Berbasis Android - Hayara Octaviani; Bambang Pramono; Rizal Adi Saputra (Department of Science and Technology Ibrahimy University, 2023)
A problem that is often encountered among Qur’an memorized is the inability to memorize verses randomly. Therefore, a system is needed that is able to train the memorization of the Qur'an memorization so that it is able to memorize even with the position of the scrambled verses. To randomize verse chunks, a method is needed that can generate random numbers. Among the algorithms capable of generating random numbers are the Linear Congruent Method and the Fisher-Yates Shuffle. Of the two algorithms, no more effective algorithm has been found. For this reason, a comparison will be made by applying algorithms to Android-based game applications with the puzzle genre. This study aims to build an educational game application with the puzzle genre on the arrangement of quranic verses by comparing the effectiveness of the Linear Congruent Method and Fisher-Yates Shuffle algorithms in randomizing verses in games. The game is run in an Android application. Based on the tests that have been carried out, the results show that Linear Congruent Method has a pattern in generating random numbers while the Fisher-Yates Shuffle does not require it, so it can be concluded that the Fisher-Yates Shuffle algorithm is the most effective in randomizing.